A Regeneration Story: From the Old Central Garage to the New City Square of Bursa - Polat, Sibel; DOSTOĞLU, NESLİHAN (My University, 2012)
Recently, many discussions have been made about the changing nature of public spaces and the loss of public life. The focal point of these discussions is the policies about the privatization and control over public spaces. In this study, the regeneration/ privatization process of a public space was stated in terms of physical, functional and semantic analysis. The case study area, presently called City Square was an old terminal complex which became an urban decay area after it lost its function in 1997. After that the Municipality organized a square project competition in this area in 2005, however it resulted to cause the area transformed to a shopping mall. Thus, this paper aimed to analyze the old Central Garage District in terms of a mixed methodology design as the combination of interpretive-historical and qualitative researches. Finally, it was determined that the area lost the public identity in terms of accessibility and use and became a controlled and semi-public courtyard of a shopping mall.

Son yıllarda dünyanın pek çok kentinde kamusal mekanların insan hayatındaki yerinin değişmesi ve kamusal yaşamın önemini kaybetmesi üzerine bir çok tartışma yapılmaktadır. Bu tartışmaların odak noktasını kamusal mekanların özelleştirilerek kontrol altına alınması oluşturmaktadır. Bu çalışmada, bir kamusal mekanın dönüşüm/özelleşme süreci, fiziksel, işlevsel ve anlamsal analizlerle ortaya koyulmaya çalışılmıştır. Çalışma alanı eski bir terminal alanı yerine yapılan Kent Meydanı’dır. Santral Garaj olarak uzun yıllar kente hizmet eden bu alan, 1997’de işlevini kaybettikten sonra bir köhneme bölgesi haline gelmiştir. 2005 yılında ise, Bursa Büyükşehir Belediyesi alanla ilgili bir meydan projesi yarışması düzenlemiş ve yarışma alanın bir alışveriş merkezine dönüşmesiyle sonlanmıştır. Çalışmada alan, yorumlayıcı-tarihsel ve nitel yöntemlerle analiz edilmiştir. Sonuç olarak, alanın erişim ve kullanım açısından kamusallık niteliğinin azaldığı, bir meydandan çok kontrollü ve yarı kamusal bir alışveriş merkezi avlusuna dönüştüğü tespit edilmiştir.
Bir Dönüşüm Hikayesi Eski Santral Garaj'dan Yeni Bursa Kent Meydanı'na
Keywords: Public Space; Urban Decay; Regeneration; Privatization; Bursa; Kamusal Mekan; Köhneme; Dönüşüm; Özelleşme